Structure and mechanical property variations in Mg–Gd–Y–Zn–Zr alloy depending on its composition and processing conditions. Issue 11 (12th April 2016) - Lapovok, Rimma; Zolotoyabko, Emil; Berner, Alex; Kauffmann, Yaron; Lakin, Eugene; Larianovsky, Natalya; Shechtman, Dan
Abstract: An effect of alloying element content on mechanical properties and precipitate formation in Mg–RE alloys was studied for Mg–8Gd–4Y–1Zn–0.4Zr (wt%) and Mg–10Gd–5Y–1.8Zn–0.4Zr (wt%). It is shown that small variations in the alloying element concentration can be used to manipulate the alloy microstructure and precipitate formation towards eliminating the asymmetry (tension/compression) and anisotropy of yield stress.